2022
DOI: 10.1007/s10071-021-01595-0
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling help-seeking and giving up: differential human-directed gazing by dogs in a modified unsolvable task paradigm

Abstract: Dogs are renowned for ‘looking back’ at humans when confronted with a problem, but it has been questioned whether this implies help-seeking or giving up. We tested 56 pet dogs from two breed groups (herding dogs and terriers) in a modified unsolvable task paradigm. One reward type (food or toy) was enclosed in a box, while the respective other reward was accessible. With both reward types, human-directed gazing in relation to the box was significantly positively correlated with interaction with the box, as lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Our results replicate the findings of various studies which have investigated differences between individual breeds in the V-detour task 19 , understanding of human gestures 7,8 , and the unsolvable task 8,18 . In contrast, most studies which have failed to find breed differences have compared breed groups 10,11,13,19,49,50 . It is possible that potential differences between breeds may have been missed in these studies, since (as shown by our current study) behavioural variation within breed groups can be substantial.…”
Section: Discussionmentioning
confidence: 98%
“…Our results replicate the findings of various studies which have investigated differences between individual breeds in the V-detour task 19 , understanding of human gestures 7,8 , and the unsolvable task 8,18 . In contrast, most studies which have failed to find breed differences have compared breed groups 10,11,13,19,49,50 . It is possible that potential differences between breeds may have been missed in these studies, since (as shown by our current study) behavioural variation within breed groups can be substantial.…”
Section: Discussionmentioning
confidence: 98%
“…Videos were analysed for behavioural measures. These measures consisted of recording the total amount of time, in seconds, that a subject gazed directly at their human handler as a measure of owner attachment [38], as well as the frequency of stress indicators performed, which included lip licking, yawning, and vocalisations such as barking or whining [39,40]. Sniffing behaviour can also be a displacement activity and an indicator of stress [41,42]; however, as we would also expect dogs to explore a new environment using olfaction, we did not include this as a stress indicator.…”
Section: Eye Contact and Stress Indicatorsmentioning
confidence: 99%
“…A third option is to consider behavioral validation of gaze responses. In a task examining canine ( Canis familiaris ) help-seeking, Hirschi et al (2022) differentiated potentially different meanings of gaze with time spent interacting with a food puzzle: They predicted that if human-directed gaze was an indication of social problem-solving, then it would be correlated with time spent interacting with the box. Alternatively, if gaze indicated giving up, then it would be negatively related to time spent on the box.…”
Section: Solutions To Current Limitationsmentioning
confidence: 99%